2011
DOI: 10.1074/jbc.m110.213330
|View full text |Cite
|
Sign up to set email alerts
|

Direct Recruitment of ERK Cascade Components to Inducible Genes Is Regulated by Heterogeneous Nuclear Ribonucleoprotein (hnRNP) K

Abstract: Components of the ERK cascade are recruited to genes, but it remains unknown how they are regulated at these sites. The RNA-binding protein heterogeneous nuclear ribonucleoprotein (hnRNP) K interacts with kinases and is found along genes including the mitogen-inducible early response gene EGR-1. Here, we used chromatin immunoprecipitations to study co-recruitment of hnRNP K and ERK cascade activity along the EGR-1 gene. These measurements revealed that the spatiotemporal binding patterns of ERK cascade transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 84 publications
2
40
0
Order By: Relevance
“…We have recently found that hnRNPK is recruited along several inducible genes with a pattern mirroring the Pol2 complex, an event that regulates the activity of the MAPK pathway components at these sites (11). To gain more insight about the role of its inducible chromatin binding we compared ChIP-Seq hnRNPK analyses of the human colon carcinoma HCT-116 line in quiescent and proliferative states.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently found that hnRNPK is recruited along several inducible genes with a pattern mirroring the Pol2 complex, an event that regulates the activity of the MAPK pathway components at these sites (11). To gain more insight about the role of its inducible chromatin binding we compared ChIP-Seq hnRNPK analyses of the human colon carcinoma HCT-116 line in quiescent and proliferative states.…”
Section: Resultsmentioning
confidence: 99%
“…Cells-HCT116 WT human colon carcinoma cells lines were grown in plastic 6-well plates in McCoy's media supplemented with 10% FBS (11). For sequencing, chromatin was isolated from 24-h serum-starved cells (0.5% FBS) and cells were stimulated for 30 min with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, NIH 3T3 cells treated with U0126 lost hnRNP-Kinduced up-regulation of MMP-3, demonstrating that the hnRNP-K-regulated cell migration is by the Ras/MEK/ERK-MMP-3 pathway. Mikula et al (46) used chromatin immunoprecipitations to study co-recruitment of hnRNP-K and ERK cascade activity along with the Egr-1 gene and found that the spatiotemporal binding patterns of ERK cascade transducers (GRB2, SOS, B-Raf, MEK, and ERK) at the EGR-1 locus resemble both hnRNP-K and RNA polymerase II. Furthermore, knockdown of hnRNP-K by siRNA decreased the level of active MEK and ERK suggesting that hnRNP-K regulates MEK and ERK as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%